2015
DOI: 10.1039/c5ra08536e
|View full text |Cite
|
Sign up to set email alerts
|

Gas sensors based on ultrathin porous Co3O4 nanosheets to detect acetone at low temperature

Abstract: Using a facile two-step process, including a hydrothermal technique and subsequently controlled annealing of the precursor, ultrathin porous Co 3 O 4 nanosheets can be synthesized. The gas sensor based on the porous Co 3 O 4 nanosheets shows a superior acetone gas-sensing performance at a low operating temperature of 150 C. The gas response to 100 ppm acetone reached 11.4, and exhibited good reproducibility. In addition, the detection limit of the Co 3 O 4 nanosheet sensor is lower than 1.8 ppm, which is the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…[14][15][16][17] Among these candidate metal oxides, cobalt-based oxides are well known because of the structured and electronic properties of spinel type oxides with variable valence states (Co 2+ /Co 3+ ) as well as the lower bonding energy of Co-O bonds, which exhibit high activity for catalytic combustion of lean methane. 18 Therefore, the cobalt-based catalysts have extensive applications in sensors, 19 lithium-ion batteries, 20 magnetic materials, 21 pigments 22 and solar cells, 23 which also show high activity for the oxidation of CH 4 , CO and VOCs due to their high redox ability and strong oxygen mobility. 24,25 It is well known that the catalytic performance of catalysts is closely related to its structure and properties, which strongly depends on the catalyst synthesis method and the types of catalyst precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Among these candidate metal oxides, cobalt-based oxides are well known because of the structured and electronic properties of spinel type oxides with variable valence states (Co 2+ /Co 3+ ) as well as the lower bonding energy of Co-O bonds, which exhibit high activity for catalytic combustion of lean methane. 18 Therefore, the cobalt-based catalysts have extensive applications in sensors, 19 lithium-ion batteries, 20 magnetic materials, 21 pigments 22 and solar cells, 23 which also show high activity for the oxidation of CH 4 , CO and VOCs due to their high redox ability and strong oxygen mobility. 24,25 It is well known that the catalytic performance of catalysts is closely related to its structure and properties, which strongly depends on the catalyst synthesis method and the types of catalyst precursors.…”
Section: Introductionmentioning
confidence: 99%
“…However, to accurately detect a specific gas within respiratory gas, an improved selectivity was required. In this context, it has been reported that the presence of nanopores in the cobalt oxide particles in addition to control over the particle shape will increase both the sensitivity and selectivity of such a system [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ZnO nanosheets, a number of other 2D metal oxide nanostructures have been tested for chemical gas sensors, such as SnO 2 , CuO, NiO, In 2 O 3 , WO 3 , and Co 3 O 4 , which exhibited good sensing properties to a variety of analytes. Zhang and Yin reported the synthesis of SnO 2 nanosheets via a simple, cost‐effective and environment‐friendly hydrothermal method at 90 °C, combined with post calcination.…”
Section: Gas Sensor Using 2d Nanostructuresmentioning
confidence: 99%